The taxonomic revision of Pleione formosana (Arethuseae, Epidendroideae, Orchidaceae) based on molecular, morphological and cytological analyses - Dai, Xiaoyu; Jiang, Mingtao; Li, Wei; Zhao, Yamei; Chen, Lei; Zhai, Junwen; Peng, Donghui; Wu, Shasha (Phytotaxa, 2020)
Due to the small degree of morphological and karyotype variations, the Pleione formosana, a well-known and valuable ornamental orchid, was treated as one member of the P. bulbocodioides complex including P. bulbocodioides, P. pleionoides and P. limprichtii, as well. The taxonomy of this complex remains problematic. P. hui was described in Anfu, Jiangxi, China, but was treated as synonym of P. formosana latter, making its taxonomic status remains controversy. In this study, we used molecular, morphological and cytological analyses to identify the relationship of P. formosana and other related species. Results base on phylogenetic analyses of chloroplast DNA and nuclear ribosomal Internal Transcribed Spacer sequence datasets indicated that Anfu samples were obviously separated from the P. formosana accessions. Network analysis showed three different groups: the P. formosana group, the P. bulbocodioides complex and the hybrid group. Morphological analysis also showed that Anfu population was significantly different from other P. formosana populations. Results of chromosome ploidy analyses showed that P. formosana was diploid and Anfu population was tetraploid, indicating that they are not the same species. In conclusion, we suggest to exclude P. formosana from P. bulbocodiodes complex, and restore the speceies rank of P. hui.